Gravidity-Dependent Production of Antibodies That Inhibit Binding of Plasmodium falciparum-Infected Erythrocytes to Placental Chondroitin Sulfate Proteoglycan during Pregnancy - O'Neil-Dunne, Iona (American Society for Microbiology, 2001)
During pregnancy, Plasmodium falciparum-infected erythrocytes sequester in the placenta by adhering to chondroitin 4-sulfate, creating a risk factor for both the mother and the fetus. The primigravidae are at higher risk for placental malaria than the multigravidae. This difference in susceptibility has been attributed to the lack of antibodies that block the adhesion of infected erythrocytes to placental chondroitin 4-sulfate in primigravid women. However, recent results show that many primigravidae at term have antibody levels similar to those of multigravidae, and thus the significance of antiadhesion antibodies in providing protection against malaria during pregnancy remains unclear. In this study, we analyzed plasma samples from women of various gravidities at different gestational stages for antiadhesion antibodies. The majority of women, regardless of gravidity, had similar levels of antibodies at term. Most primigravidae had low levels of or no antiadhesion antibodies prior to ∼20 weeks of pregnancy and then produced antibodies. Multigravidae also lacked antibodies until ∼12 weeks of pregnancy, but thereafter they efficiently produced antibodies. In pregnant women who had placental infection at term, higher levels of antiadhesion antibodies correlated with lower levels of placental parasitemia. The difference in kinetics of antibody production between primigravidae and multigravidae correlated with the prevalence of malaria in these groups, suggesting that antibodies are produced during pregnancy in response to placental infection. The early onset of efficient antibody response in multigravidae and the delayed production to antibodies in primigravidae appear to account for the gravidity-dependent differential susceptibilities of pregnant women to placental malaria.